Magic trait Electric Organ Discharge (EOD) <subtitle>Dual function of electric signals promotes speciation in African weakly electric fish</subtitle> - Philine G.D. Feulner; Martin Plath; Jacob Engelmann; Frank Kirschbaum; Ralph Tiedemann (Communicative & Integrative Biology, 2009)
A unique evolutionary specialization of African weakly electric fish (Mormyridae) is their ability to produce and perceive electric signals. Mormyrids use their Electric Organs Discharge (EOD) for electrolocation and electrocommunication. Here we discuss the adaptive significance of the EOD in foraging (electric prey detection) in light of recent results demonstrating that mormyrid fish mate assortatively according to EOD waveform characteristics (electric mate choice). Therefore the EOD as a single trait pleiotropically combines natural divergent selection and reproductive isolation. Consequently we postulate the EOD as a “magic trait” promoting the diversification of African weakly electric fish.